Genotypes and Haplotypes of TIM-3 Gene and Risk of Tuberculosis - Jwan Ahmed Al Hamawandi (Journal of Global Pharma Technology, 2017)
Tuberculosis is a cosmopolitan infectious disease caused by Mycobacterium tuberculosis. The disease outcome depends largely on the activity of T-lymphocytes. Certain variants in TIM-3 gene may influence the activity of these cells against the causative agent. To assess the influence of three single nucleotide polymorphisms in the TIM-3 gene on the susceptibility to pulmonary tuberculosis this case/control study included 68 patients with pulmonary tuberculosis and 40 apparently healthy controls. DNA was extracted from blood samples obtained from each participant. The flanking regions in TIM-3 gene promoter for -1541 C/T, -1516 G/T and -574 A/C were amplified which PCR using specific primers. Allele-specific PCR or restriction fragment length polymorphism used for Genotyping.Keywords: Pulmonary tuberculosis, TIM-3 gene, single nucleotide polymorphism.